Pituitary macroadenoma resulting from primary hypothyroidism: A16-year-old girl - Zahra Davoudi; Arezoo Chouhdari; Omidvar Rezaee; Guive Sharifi (Babol University of Medical Sciences, 2019)
Background: Primary hypothyroidism is a common medical condition. It can lead to pituitary adenoma which is usually asymptomatic, but it can also lead to symptomatic macroadenomas which are hard to diagnose due to different clinical presentations. Case presentation: A 16-year-old girl presented for endocrinology consultation prior to neurosurgical operation. She had galactorrhea which was accompanied by vertigo & low grade blurred vision without a headache and was diagnosed with pituitary macroadenoma and was planned for a surgery. She had TSH level of more than 100 mU/L, free thyroxine of 1.9 pmol/L. Her thyroid peroxidase (TPO) antibody level was 13.3 IU/mL, insulin growth factor-1 392 µ/l and serum prolactin level 42 ng/ml. During physical exam and with the laboratory findings, we suspected for a primary hypothyroidism as the leading cause of pituitary macroadenoma. As the result, we cancel the surgery and start levothyroxine therapy 100µg daily for her. In the follow-up it revealed that our diagnosis was correct and she went into remission with pituitary gland shrinking and decreasing TSH and prolactin levels. Conclusion: It is important to understand the different presentation of primary hypothyroidism to decrease the unnecessary risk of maltreatment in patients.